Inpatient Rehabilitation Outcomes After Severe COVID-19 Infections: A Retrospective Cohort Study. (December 2021) - Abramoff, Benjamin A.; Dillingham, Timothy R.; Caldera, Franklin E.; Ritchie, Marylyn D.; Pezzin, Liliana E.
Abstract : Objective: The aim of the study was to describe the characteristics and functional outcomes of patients undergoing acute inpatient rehabilitation after hospitalization for COVID-19. Design: Using a retrospective chart review, patients were identified who were admitted to inpatient rehabilitation after COVID-19. Patient information collected included sociodemographic characteristics, comorbidities, length of stay, discharge disposition, self-care, mobility, and cognitive functioning. These patients were compared with patients (controls) without COVID-19 with similar impairment codes treated at the same facility before the COVID-19 pandemic. Results: There were 43 patients who were admitted to the inpatient rehabilitation hospital after COVID-19 infection and 247 controls. Patients who had COVID-19 were significantly more likely to be African American and to have been admitted to a long-term acute care hospital. They also had a longer length of rehabilitation stay. The groups did not differ by age, sex, or insurance. Functionally, although presenting with significantly worse mobility, self-care, and motor scores, the patients previously infected with COVID-19 had similar functional outcomes at time of discharge to the control group. Conclusions: Although patients with a history of COVID-19 had worse function at time of admission to acute rehabilitation, inpatient rehabilitation significantly improved their function to comparable levels as patients who did not have COVID-19. To Claim CME Credits: Complete the self-assessment activity and evaluation online at http://www.physiatry.org/JournalCME CME Objectives: Upon completion of this article, the reader should be able to: (1) Identify how characteristics of patients with COVID-19 admitted to acute rehabilitation differ from those with similar admission codes but without COVID-19; (2) Describe changes in functional measures at admission and discharge of COVID-19 patients compared with patients without COVID-19; and (3) Recognize how inpatient rehabilitation may help reduce inequities in outcomes after severe COVID-19 infection. Level: Advanced Accreditation: The Association of Academic Physiatrists is accredited by the Accreditation Council for Continuing Medical Education to provide continuing medical education for physicians. The Association of Academic Physiatrists designates this Journal-based CME activity for a maximum of 1.0 AMA PRA Category 1 Credit(s) ™. Physicians should only claim credit commensurate with the extent of their participation in the activity. Abstract : Supplemental digital content is available in the text.